* Trans(ing) Body Art: Cutting Potential & Trans Embodied Labor - Møller Madsen, Storm (Peripeti, 2018)
This article engages with a number of trans artists who have turned to the genre of body art, using their explicit body as the focal point of their work. The article engages the subgenre of trans body art and reads the performances Ritual (Marriage) by Leah James and Mars Hobrecker and Homage by Kris Grey through the notion of the cut to examine the disciplining of corporeality and trans embodied labor and how these are/can be challenged and (re)imagined through performance.